Nonfucosylation of an anti-TIGIT antibody enhances FcγR engagement, driving innate immune activation and antitumor activity - Alyson J. Smith; Robert E. Thurman; Weiping Zeng; Bryan Grogan; Sasha Lucas; Guadalupe Gutierrez; Ryan A. Heiser; Serena W. Wo; Amber Blackmarr; Scott Peterson; Shyra J. Gardai (Frontiers in Immunology, 2023)
TIGIT is an immune checkpoint receptor expressed on activated and memory T cells, immunosuppressive T regulatory cells, and natural killer (NK) cells. TIGIT has emerged as an attractive target for antitumor therapies, due to its proposed immunosuppressive effects on lymphocyte function and T cell activation. We generated an anti-TIGIT monoclonal antibody (mAb) that binds with high affinity to human, non-human primate, and murine TIGIT and through multiple experimental methodologies demonstrated that checkpoint blockade alone is insufficient for antitumor activity. Generating anti-TIGIT mAbs with various Fc backbones we show that muting the Fc-Fcγ receptor (FcγR) interaction failed to drive antitumor activity, while mAbs with Fc functional backbones demonstrate substantial antitumor activity, mediated through activation of antigen-presenting cells (APCs), T cell priming, and NK-mediated depletion of suppressive Tregs and exhausted T cells. Further, nonfucosylation of the Fc backbone resulted in enhanced immune responses and antitumor activity relative to the intact IgG1 backbone. The improved activity correlated with the biased FcγR interaction profile of the nonfucosylated anti-TIGIT mAb, which supports that FcγRIIIa binding with decreased FcγRIIb binding favorably activates APCs and enhances tumor-specific CD8+ T cell responses. The anti-TIGIT mAbs with intact FcγR interacting backbones also demonstrated synergistic enhancement of other standard antitumor treatments, including anti-PD-1 treatment and a model monomethyl auristatin E antibody–drug conjugate. These findings highlight the importance of the anti-TIGIT mAb’s Fc backbone to its antitumor activity and the extent to which this activity can be enhanced through nonfucosylation of the backbone.